The Main Task of the New Uzbekistan is to Increase the Legal Literacy and Culture of Young People - Jumaev Sarvarbek (Research Parks Publishers, 2021)
this article describes more broadly the reforms in the education system and new theologies in the teaching of legal sciences, the results of the analysis.